Influence of springtime biomass burning in South Asia on regional ozone (O3): A model based case study. (January 2015) - Jena, Chinmay; Ghude, Sachin D.; Pfister, G.G.; Chate, D.M.; Kumar, Rajesh; Beig, G.; Surendran, Divya E.; Fadnavis, S.; Lal, D.M.
Abstract: In this study, for the first time, the influence of springtime (MAM) biomass burning in South Asia on regional ozone (O3 ) distribution has been evaluated using a regional chemical transport model (WRF-Chem) and the Fire Inventory from NCAR (FINNv1). Model results are compared with satellite retrievals of tropospheric column amounts of carbon monoxide (CO) from MOPITT and nitrogen dioxide (NO2 ) from OMI. With daily varying emissions, the model captures reasonably well the satellite-derived temporal variations in CO and NO2 (index of agreement ( R ) for CO is 0.83 and for NO2 is 0.76), indicating the effectiveness of the model in estimating the overall fire impact on a regional scale. Simulated tropospheric NO2 concentration shows better agreement with the magnitude of observed NO2 when FINNv1 NO x emissions are reduced by a factor of 2.2 over the model domain. A clear increase in CO and NO2 levels over Burma (35–60%), Central India (15–30%), the Indo-Gangetic (15–25%) region and the Bay of Bengal (15–40%) are simulated with fire emissions. The model results are also used to quantify the net O3 production from fires. Calculated O3 productions are up to 4 ppb h − 1 over inland and up to 0.1 ppb h − 1 over marine regions respectively. Our model-based analysis yields average enhancement ratios ΔO3 /ΔCO of 0.12 ppbv/ppbv and a total O3 production of about 3.5 Tg from South Asia during the spring season. The findings demonstrate that the springtime fire emissions in South Asia have a noticeable impact on the O3 in this region. Highlights: Fire emissions in South Asia have a noticeable impact on the O3 in this region. Simulations with fire emissions show better agreement with observations. Surface O3 production of 3.5 Tg is estimated during spring season.